SUMBANGSIH PENDIDIKAN AGAMA KRISTEN BAGI KEADILAN DIFABILITAS [THE CONTRIBUTION OF CHRISTIAN EDUCATION TO DISABILITY JUSTICE] - Paulus Eko Kristianto (Polyglot, 2019)
How does Christian education contribute to disability justice? This is the question that guided the author when writing this article. Christian education is at the core of students’ formation. Students are invited not only to master knowledge, but also a theological perspective that they can apply to issues and problems. In mapping and responding to this, the author conducted a literature study of the Christian education curriculum used in schools of the Christian education working group of the churches in Indonesia. The results of this study indicates that  disability theology is an issue that has not been discussed comprehensively in the Christian education curriculum in schools, although it has been discussed explicitly at a minimal level.BAHASA INDONESIA ABSTRAK: Bagaimana sumbangsih pendidikan agama kristen bagi keadilan difabilitas? Pertanyaan ini menjadi pokok permasalahan dan panduan dalam penulisan artikel ini. Pendidikan agama kristen merupakan inti pembentukan peserta didik. Peserta didik diajak tidak hanya menguasai ilmu yang tinggi, melainkan teologi yang mampu berdialog dengan konteks mereka. Dalam memetakan dan menanggapi permasalahan tersebut, penulis melakukan penelitian studi pustaka terhadap kurikulum pendidikan agama kristen di sekolah dari kelompok kerja pendidikan agama Kristen persekutuan gereja-gereja di Indonesia. Hasil penelitian tersebut menunjukkan bahwa isu teologi difabilitas belum dibahas secara komprehensif dalam kurikulum PAK di sekolah, walaupun sudah dibahas secara eksplisit dalam kadar minim.